K channels are expressed early in human T-cell development. - Schlichter, L (1986)
Mature human T lymphocytes proliferate in response to the mitogen phytohemagglutinin (PHA), but immature thymocytes lacking the T3 receptor (T3- thymocytes) do not. Because functioning K channels are required for proliferation of mature T cells, we asked whether immunoincompetent T3- thymocytes lack normal K channels. We report that T3- thymocytes have a K+ current similar to that of mature peripheral T cells--that is, similar voltage dependence, activation and inactivation kinetics, and pharmacology. Moreover, the maximal specific K+ conductance is the same for both cell types, implying a similar density of activable channels in each cell. In assessing the functional responses of the channels to PHA, we found that the K+ current of immature and mature cells responds similarly to the mitogen. Responses near the threshold voltage for activating the K+ current were variable; the K+ conductance and rate of activation were increased, decreased, or unchanged after PHA treatment. For several cells, the voltage dependence of the conductance and activation kinetics was shifted in opposite directions. At more positive voltages, PHA consistently caused a 10-20% suppression of conductance that was not due to the addition of an inward current, to changes in the time course of activation or inactivation, or to changes in the steady-state level of inactivation. The effects of PHA on the K+ current cannot be explained by a simple shift in surface potential, as has been hypothesized to be involved in its triggering of T-cell proliferation. Taken together, our findings show K channels are expressed very early in T-cell differentiation, possibly before thymic processing, differential responses of the K+ current to PHA do not account for the failure of T3- thymocytes to proliferate, and changes in surface potential are probably not a necessary early event in activation of T cells by PHA.